The translator’s subjectivity in disseminating Chinese culture : a case study on the English translations of Cha Jing - Zheng, Han (Nanyang Technological University, 2020)
As the world’s first treatise on tea, Cha Jing (茶经, The Classic of Tea) written in China’s Tang Dynasty is the embodiment of ancient Chinese culture, featuring a collection of the essential Chinese philosophies of Confucianism, Taoism, and Buddhism. Translating this ancient Chinese classic facilitates the spread of Chinese culture to the world, which has been conducted by translators both in and outside China. Since a translation is a translator’s conscious creation under certain circumstances, the translator’s subjectivity will inevitably affect the translation results. This thesis sets to explore the translator’s subjectivity in disseminating Chinese culture through a case study on two English translations of Cha Jing. One is produced by Francis Ross Carpenter, an American translator. The other is produced by Chinese translators Jiang Yi and Jiang Xin.